IMPLEMENTATION OF INTEGRATIVE THEMATIC LEARNING IN ISLAMIC EDUCATION AND CIVIL SUBJECTS AT SD N GIRIWUNGU BANTUL YOGYAKARTA - Isti Faidatul Amanah; Muhammad Asrofi (STAI Asy-Syukriyyah, 2023)
This research explored the implementation of integrative thematic learning in Islamic Education (PAI) and Characteristics at SD N Giriwungu Bantul, Yogyakarta. Researchers used qualitative research methods. The research results showed several stages in implementing integrative thematic learning, including 1) Planning the RPP in detail, 2) carrying out two stages, namely core and closing material, and 3) Assessing the implementation results in various stages. The obstacles teachers faced in integrative thematic learning were the need for more learning media provided by the school and the unavailability of thematic teaching materials (books).